(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Background: The purpose of this study was to investigated cases of spinal cord injury (SCI) during the years 2017-2021, in Constanta County (Romania) to update the data on SCI and thus identify the SCI trends in this region of Romania. Methods: The study retrospectively analysed patients with SCI in Constanța County, whose data (medical records) were provided to us by the Romania Motivation Foundation. This analysis was made for the period January 1, 2017 - August 31, 2021. Results: Ninety-six new traumatic cases of SCI were reported between 2017 and 2021 in Constanța County. It was found that the annual incidence is 2.48 per hundred thousand inhabitants. The male / female ratio was 5:1 and the mean age at injury was 33.52 ± 15.1 (33.41 ± 14.80 for men and 33.92 ± 16.01 for women). The most common cause of injury was unintentional fall (48.95%), followed by road accidents (39.58%), stab wounds (4.16%), gunshot wounds (3.12%) and injuries caused by diving 2.08%). Fifteen patients (15.62%) were quadriplegic, and 81 patients (84.37%) were paraplegic. The most common level of lesions was C4 (33.33%) in tetraplegics and T12 (25.92%) in paraplegics. The most common associated injury was head trauma (15.8%), followed by limb fractures (9.5%). The incidence rate of SCI in Constanta County increased (p <0.05) and the highest increase in the incidence of spinal cord injuries was observed among patients in the age groups 29 - 49 years. Conclusions: Due to the existence of limitations, it is difficult to obtain accurate epidemiological data for SCI. Therefore, more studies are needed to provide a large amount of data and evidence. Our data indicate the need to take measures both for prevention and to provide specialized care for this type of traumatic pathology. Keywords: spinal cord injury; traumatic; incidence; unintentional falls; Constanta County (Romania).